2018
DOI: 10.1073/pnas.1801512115
|View full text |Cite
|
Sign up to set email alerts
|

Volatile biomarkers of symptomatic and asymptomatic malaria infection in humans

Abstract: SignificanceMalaria elimination efforts are hindered by the prevalence of asymptomatic infections, which frequently go undetected and untreated. Consequently, there is a pressing need for improved diagnostic screening methods. Based on extensive collections of skin odors from human populations in Kenya, we report broad and consistent effects of malaria infection on human volatile emissions. Furthermore, we found that predictive models based on machine learning algorithms reliably determined infection status ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 37 publications
1
69
1
Order By: Relevance
“…Environmental factors and personal habits can also influence skin volatile composition, including level of physical activity, personal hygiene, and cosmetic or fragrance usage [9]. Monitoring skin volatiles offers a non-invasive route towards probing pathophysiological status and monitoring therapy, and research in this area to date has primarily focused on internal or systemic disease states for which consistent data has emerged on clinically important skin volatiles, including diabetes [17], hepatic disease [18] and malaria [19].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors and personal habits can also influence skin volatile composition, including level of physical activity, personal hygiene, and cosmetic or fragrance usage [9]. Monitoring skin volatiles offers a non-invasive route towards probing pathophysiological status and monitoring therapy, and research in this area to date has primarily focused on internal or systemic disease states for which consistent data has emerged on clinically important skin volatiles, including diabetes [17], hepatic disease [18] and malaria [19].…”
Section: Introductionmentioning
confidence: 99%
“…Ten volatiles including ethyl-cyclohexane, ethyl-benzene, m-xylene or p-xylene, o-xylene, propylcyclohexane, 1-ethyl-3-methylbenzene, decane, nonanal, and two unidentified compounds were released at significantly higher amounts in asymptomatic compared to uninfected individuals. In symptomatic individuals, amounts of six compounds, namely, 2,4-dimethylhept-1-ene, 1-ethyl-3-methylbenzene, 1,2,4-trimethylbenzene, decane, s(-)-limonene, and 2-ethylhexan-1-ol were significantly higher compared to those in uninfected individuals (Figure 2) [31]. These studies highlighted that the mature gametocyte (sexual stage of the parasite in human blood) could have been the key contributor to the VOCs [50], chemical codes which communicate between mosquito and parasite to enhance the efficiency of parasite transmission (Figure 2).…”
Section: Plasmodium Induced Volatile Organic Compounds (Vocs) and Mosmentioning
confidence: 98%
“…Human malaria parasites alter the probing and persistence behavior of mosquitoes, resulting in increased transmission [28]. There is also evidence that parasites and their metabolites affect both mosquito and human host physiology and behavior to increase the probability of transmission [11,21,[29][30][31][32][33]. In rodent and bird malaria model systems, infected hosts have been found to be more attractive to mosquitoes [30,34].…”
Section: Parasite-vector Interplay For the Transmission Successmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite such importance, most studies of Triatominae biology have been concentrated in a handful of species, and attention to the knowledge of animals from natural populations is currently scarce. Recent research in several vector transmitting neglected diseases, including Triatominae bugs, have demonstrated that basic knowledge about vectors' biology and zoonosis helps to find potential solutions to minimize transmission risk (De Moraes et al, 2018;Rojas-de Arias et al, 2017), and phenotypic traits can indirectly provide ecological information to understand vector-parasite ecology (Nattero et al, 2017). For example, Miura et al (2006) found in a trematode-snail host system that infected snails were markedly larger and exhibited different shell morphology than non-infected individuals.…”
Section: Introductionmentioning
confidence: 99%